• Support PF! Buy your school textbooks, materials and every day products Here!

Kinetic Energy of a jogger problem

  • Thread starter destinc
  • Start date
  • #1
17
0
Jogger A has a mass m and a speed v, jogger B has a mass m/2 and a speed 3v, jogger C has a mass 3m and a speed v/2 and jogger D has a mass 4m and a speed v/2. Rank the joggers in order of increasing kinetic energy. Indicate ties where appropriate

I started with KE formula, KE=1/2mv^2 and plugged in values for each jogger
Jogger A KE=1/2mv^2
Jogger B KE=1/2(m/2)(3v)^2 which = 2.25mv^2
Jogger C KE=1/2(3m)(v/2)^2 which =6mv^2
Jogger D KE=1/2(4m)(v/2)^2 which =8mv^2

Based on this I ranked them in increasing order A,B,C,D
The answer given is, D<A = D<B
I'm not sure I understand the answer, and I don't see where I went wrong.
Thank you for any help.
 

Answers and Replies

  • #2
gneill
Mentor
20,792
2,770
Jogger A has a mass m and a speed v, jogger B has a mass m/2 and a speed 3v, jogger C has a mass 3m and a speed v/2 and jogger D has a mass 4m and a speed v/2. Rank the joggers in order of increasing kinetic energy. Indicate ties where appropriate

I started with KE formula, KE=1/2mv^2 and plugged in values for each jogger
Jogger A KE=1/2mv^2
Jogger B KE=1/2(m/2)(3v)^2 which = 2.25mv^2
Jogger C KE=1/2(3m)(v/2)^2 which =6mv^2
Jogger D KE=1/2(4m)(v/2)^2 which =8mv^2

Based on this I ranked them in increasing order A,B,C,D
The answer given is, D<A = D<B
I'm not sure I understand the answer, and I don't see where I went wrong.
Thank you for any help.


Check your math for joggers C and D.
 
  • #3
Doc Al
Mentor
44,892
1,143
I started with KE formula, KE=1/2mv^2 and plugged in values for each jogger
Jogger A KE=1/2mv^2
Jogger B KE=1/2(m/2)(3v)^2 which = 2.25mv^2
Good.
Jogger C KE=1/2(3m)(v/2)^2 which =6mv^2
Jogger D KE=1/2(4m)(v/2)^2 which =8mv^2
Redo these.
 
  • #4
17
0
Jogger C KE=1/2(3m(v/2)^2 = 3/2m(v^2)/4 = 3/8mv^2
Jogger D KE= 1/2(4m)(v/2)^2 = 1/2mv^2
Which means D=A and both > C > B
Which still isn't the given answer
 
  • #5
gneill
Mentor
20,792
2,770
Jogger C KE=1/2(3m(v/2)^2 = 3/2m(v^2)/4 = 3/8mv^2
Jogger D KE= 1/2(4m)(v/2)^2 = 1/2mv^2
Which means D=A and both > C > B
Which still isn't the given answer
List all four results now that you've recalculated.
 
  • #6
Doc Al
Mentor
44,892
1,143
Jogger C KE=1/2(3m(v/2)^2 = 3/2m(v^2)/4 = 3/8mv^2
Jogger D KE= 1/2(4m)(v/2)^2 = 1/2mv^2
Right.
Which means D=A
OK.
and both > C > B
Rethink that.
 
  • #7
17
0
Jogger A KE= 1/2mv^2
Jogger B KE= 2.25mv^2
Jogger C KE= 3/8mv^2
Jogger D KE=1/2mv^2

Oh C< D=A < B Still not the answer
Thanks again for all this help
 
  • #8
Doc Al
Mentor
44,892
1,143
The answer given is, D<A = D<B
Obviously a typo here. Better check it. (that first D should be a C)
 
  • #9
17
0
I really don't understand the format of the given answer, could one of you translate, why don't they give value of C in the answer?
 
  • #10
17
0
ahhhhh, Typo is in book. Thanks for the help
 

Related Threads for: Kinetic Energy of a jogger problem

  • Last Post
Replies
3
Views
3K
  • Last Post
Replies
1
Views
1K
  • Last Post
Replies
5
Views
4K
Replies
2
Views
2K
  • Last Post
Replies
2
Views
9K
  • Last Post
Replies
2
Views
1K
  • Last Post
Replies
2
Views
3K
Top